Combined effects of TGFB1 +869 T/C and +915 G/C polymorphisms on acute rejection risk in solid organ transplant recipients: a systematic review and meta-analysis. - Yu-Zheng Ge; Ran Wu; Tian-Ze Lu; Rui-Peng Jia; Ming-Hao Li; Xiao-Fei Gao; Xiao-Min Jiang; Xian-Bo Zhu; Liang-Peng Li; Si-Jia Tan; Qun Song; Wen-Cheng Li; et al. (PLoS ONE)
Background Transforming growth factor-beta 1(TGF-β1) is involved in the development of acute rejection (AR) episodes in solid organ transplant recipients; and a number of studies have been conducted to investigate the combined effects of human TGF-β1 gene (TGFB1) +869 T/C and +915 G/C polymorphisms on AR risk. However, the results obtained are inconclusive. Methods Eligible studies that investigated the haplotypic association between TGFB1 +869 T/C and +915 G/C polymorphisms and AR risk were comprehensively searched in the PUBMED, EMBASE, China National Knowledge Infrastructure, and Wanfang Database. Statistical analyses were performed by using STATA 12.0 and Review Manager 5.0. Results Fourteen eligible studies with 565 AR cases and 1219 non-AR cases were included. Overall, a significantly decreased risk was detected in patients carried with intermediate producer (IP) haplotypes (T/C G/C, T/T G/C, and C/C G/G) and/or low producer (LP) haplotypes (C/C G/C, C/C C/C, T/T C/C, and T/C C/C) compared with high producer (HP) haplotypes (T/T G/G and T/C G/G; IP vs. HP: OR = 0.75, 95% CI, 0.58-0.96, P heterogeneity  = 0.238; IP/LP vs. HP: OR  = 0.77, 95% CI, 0.61-0.98, P heterogeneity  = 0.144). In addition, subgroup analysis by transplant types demonstrated a similar association in patients receiving heart transplant (IP vs. HP: OR  = 0.32, 95% CI, 0.14-0.73, P heterogeneity  = 0.790; IP/LP vs. HP: OR  = 0.41, 95% CI, 0.20-0.85, P heterogeneity  = 0.320). Conclusions The current meta-analysis and systematic review indicated that recipient TGFB1 HP haplotypes were significantly associated with an increased risk for AR in solid organ transplant recipients, particularly patients receiving cardiac allograft.